The use of language in mathematics teaching in primary schools in Malawi: bringing language to the surface as an explicit feature in the teaching of mathematics - Kaphesi, Elias S. (2002)
The aim of this study was to explore how teachers use language in Chichewa medium and English medium mathematics teaching in standards 3 and 4 of selected primary schools in Zomba, Malawi. Chichewa is a local and national language whereas English is a foreign language yet the official language in Malawi. Chichewa is a language of instruction in standards 1to 4 whereas English is used from standard 5. Both Chichewa and English are subjects of study from standard 1. Issues investigated included: teacher understanding of the use of Chichewa or English in mathematics teaching; teachers' knowledge and use of mathematics vocabulary in Chichewa and in English; and teacher use of language in mathematics lessons. In this thesis, I develop a sociolinguistic approach to a study of teachers' perceptions and uses of language in mathematics teaching. I demonstrate how we can represent these perceptual structures using sociolinguistic tools and principles, which I use to study how 40 mathematics teachers linguistically organise and structure their teaching of mathematics. I adopt the position that teaching is fundamentally a language activity based on classroom communication activities which are fundamentally sociolinguistic in character, that sociolinguistic structures are dynamic and rational, yet exhibit a level of stability which results in diverse teacher dispositions gelling into conflicting tensions. I develop a theoretical base and iteratively explore this, evolving a description of how we might model what I call the sociolinguistic orientation of mathematics teachers. I construct theoretical, conceptual and methodological frameworks to enable me to study some of the underlying relationships among the tensions, teacher predispositions and the sociolinguistic environment in the classroom. I draw on a constructivist approach to mathematics education founded in Piagetian and Vygotskian theories and in particular draw on the concepts of coping strategies (Edwards and Furlong, 1987) to deal with the dynamics of classroom communications (Hills, 1969) which result in tensions in the use of language in mathematics teaching Pimm, 1987; Adler, 2001}. I begin by educationally, professionally and linguistically locating myself before moving on to looking at how we can understand communication in the mathematics classroom, the role of language in mathematics education with emphasis on bilingual mathematics education. I examine theories for understanding the interplay and interrelationship among teaching, communication, language use, and mathematics and bilingual classroom. Thereafter I look at the sociolinguistic roots of mathematics education in the Malawi Education System, identifying those areas where the current language policy in education does not consider the role of language in mathematics education. I draw heavily on sequential focus group discussion, interviews, tests and classroom observations and construct a perceptual model for the sociolinguistic orientation of 40 mathematics teachers towards use of Chichewa or English, and explore how these perceptions relate to the actual use of language in bilingual mathematics classrooms. To increase the validity of the data and findings, I used methodological and data triangulation. The findings of the study suggest that the sociolinguistic orientation of mathematics teachers relates to the linguistic nature of mathematics (the desire to teach the technical language as opposed to the ordinary language that pupils will easily understand), mystifying language policy in education (the inconsistency of language policy), dynamic classroom discourse (the multi-functions of language in the classroom) and inconsistent source of language for use in mathematics teaching (different competencies in language for teaching and learning among teachers, pupils and instructional materials). In addition, I illustrate how the teacher sociolinguistic orientation depends on whether the language of instruction is L1 or L2 which rest ideologically on code switching between Chichewa and English as well as marked difference in the patterns of language use between Chichewa and English medium mathematics lessons. The findings of the study can increase our understanding of the dynamics of mathematics classroom discourse by not only identifying more tensions in the use of language hut also the sources of these tensions. These might pave the way to find remedies to reduce the linguistic tensions in mathematics education. These findings imply that teachers need to be trained and supported in the use of language if they are to improve the teaching of mathematics. It is recommended that a programme he developed to train and orient teachers in the use of language in mathematics teaching, and to produce appropriate instructional materials that would assist teachers and pupils to use language effectively in mathematics.